Investigation on Impact of Changes in Land Cover Patterns on Surface Runoff in Ayung Watershed, Bali, Indonesia Using Geographic Information System: 10.32526/ennrj/20/202100161 - Dharmayasa, I Gusti Ngurah Putu; Surakit, Kritsanat; Jindal, Ranjna; Thongdara, Romanee (Environment and Natural Resources Journal, 2022)
Population growth, urbanization, and infrastructure development activities have resulted in the land conversion of forests and farmlands to residential and commercial zones. Such land conversion causes changes in the land cover, as experienced in the Ayung Watershed, in the island of Bali, Indonesia. Here, the land cover undergoes rapid changes due to the growing tourism sector, affecting the runoff coefficient. This study evaluated the changing land cover patterns and surface runoff in the Ayung Watershed between 2012 and 2019. An increase in the surface runoff during the high rainfall events may lead to flooding in the area. The identification of land change patterns in the Ayung Watershed was carried out by a manual digitizing process on Google Earth maps. The runoff coefficient was calculated by Cook’s method using the four physical characteristics of the watershed: land cover, infiltration rate, land slope and drainage density; showing significant changes in the land cover in the study area. Farmlands and forests were reduced by 647.8 ha and 553.1 ha respectively, converted into fast growing grasslands or unproductive land. Such land cover changes have a negative impact by increasing the runoff coefficient in the area. During the study period, the runoff coefficient was consistently found to be more than 0.6 (high-risk category). Several sections in the city of Denpasar experienced an increase in the runoff coefficient by more than 5%. Consequently, there was a high-risk of flooding in the area because of the increasing surface runoff.